Ensuring the credibility and sharia compliance of sovereign green sukuk to achieve net zero emissions in Indonesia - Baity, Sheila Noor; Rachmiati Poetri, Titie (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2025)
This study examines how the government maintains green sukuk credibility through POJK 18/2023, the SDGs Government Securities Framework, and the alignment of issuance and reporting with Sharia principles. A qualitative-descriptive approach was applied, using data from interviews, observations, and document analysis. Findings reveal that while sustainable finance regulations and frameworks exist, gaps remain in ensuring transparency and the use of objective indicators. There is also a lack of standardized Sharia guidelines concerning substantive compliance, resulting in a formalistic focus on akad. OJK and Sharia Supervisory Boards (DPS) should strengthen oversight during issuance and post-issuance, particularly in reviewing the prospectus and impact reports. This study emphasizes the need for stricter sanctions, transparency on the methods of project selection and impact reporting, and the integration of al-Ḍarar Yuzāl and Maṣlaḥah principles to ensure green sukuk are not only legal but also ethical and impactful. Public interest statements This study explores how government regulations and Sharia (Islamic law) principles are used to maintain the credibility of green sukuk. It also highlights concerns about greenwashing, where projects claim to be “green” without real impact. The findings call for stronger oversight, penalties, clear reporting standards, and ethical guidelines to ensure that public funds contribute to meaningful environmental and social impact. This research matters because it connects the concept of sharia with sustainability in ways that impact the development of sustainable financing in Indonesia.